Effectiveness of Acceptance and Commitment Therapy on Cognitive Fusion and Social Anxiety in Women with Generalized Anxiety Disorder - Enayati Shabkolaei, Maryam; Salehani, Zeinab; Lesani, Saeid (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The purpose of this study was to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on cognitive fusion and social anxiety in women suffering from generalized anxiety disorder. Methods: This study was an applied, quasi-experimental design with pre-test, post-test, and follow-up, including a control group. The population consisted of all women with generalized anxiety disorder who attended counseling centers in Sari city. The sample included 30 women with generalized anxiety disorder, selected via convenience sampling and randomly assigned to two groups: the experimental group receiving ACT for social anxiety disorder (Hayes, 2012) and a wait-list control group. Data were collected using the Social Anxiety Questionnaire (Watson & Friend, 1969) and the Cognitive Fusion Questionnaire (Gillanders, 2014). Data were analyzed using repeated measures ANOVA with SPSS-26 software. Findings: The results showed significant differences between the ACT treatment group and the control group. ACT was effective in reducing cognitive fusion (F = 15.25, p < .001) and social anxiety (F = 38.86, p < .001) in women with generalized anxiety disorder (p < .001). Conclusion: Therefore, it can be concluded that Acceptance and Commitment Therapy may serve as an effective intervention method for improving cognitive fusion and social anxiety in women with generalized anxiety disorder.